2016
DOI: 10.18632/oncotarget.9504
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotube formation is stimulated by hypoxia in ovarian cancer cells

Abstract: In this study, we demonstrated that hypoxic conditions stimulated an increase in tunneling nanotube (TNT) formation in chemoresistant ovarian cancer cells (SKOV3, C200). We found that suppressing the mTOR pathway using either everolimus or metformin led to suppression of TNT formation in vitro, verifying TNTs as a potential target for cancer-directed therapy. Additionally, TNT formation was detected in co-cultures including between platinum-resistant SKOV3 cells, between SKOV3 cells and platinum-chemosensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 34 publications
7
110
0
1
Order By: Relevance
“…The biogenesis and release of exosomes could be impaired by dimethyl amiloride and inactivation of the small GTP‐binding protein ARF6, respectively . Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported . Second, post‐transcriptional RNA interference by HLA‐G‐specific miRNAs (such as miR‐148, miR‐152, miR‐548q and miR‐628‐5p) has been demonstrated to reduce HLA‐G expression and recover NK cell lysis of tumor cells .…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 67%
See 1 more Smart Citation
“…The biogenesis and release of exosomes could be impaired by dimethyl amiloride and inactivation of the small GTP‐binding protein ARF6, respectively . Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported . Second, post‐transcriptional RNA interference by HLA‐G‐specific miRNAs (such as miR‐148, miR‐152, miR‐548q and miR‐628‐5p) has been demonstrated to reduce HLA‐G expression and recover NK cell lysis of tumor cells .…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 67%
“…70,71 Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported. 72,73 Second, post-transcriptional RNA interference by HLA-G-specific miRNAs (such as miR-148, miR-152, miR-548q and miR-628-5p) has been demonstrated to reduce HLA-G expression and recover NK cell lysis of tumor cells. 74 Third, the masking of either HLA-G or receptor ILTs with specific blocking antibodies could be a promising strategy for HLA-G/ILTs-based target therapy.…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 99%
“…With the development of biotechnology, the changes for some functional proteins have been revealed in CRC tissues [24]. Hypoxia is prognostically important in cancer therapy and it has a deep impact on malignant development of various cancers [5, 6]. HIF-1 (hypoxia inducible factor-1), a kind of hydrocarbon nuclear translators, plays an important role in oxygen homeostasis [7] and consists of two subunits, HIF-1 alpha and HIF-1 beta.…”
Section: Introductionmentioning
confidence: 99%
“…However, with ovarian cancer cells, there was notable heterogeneity in the rate of TNT formation among cancer cell lines and benign ovarian epithelial cells. Although platinum‐chemoresistant cells (C200 and SKOV3 cell lines) were increased over chemosensitive and normal epithelial cells (A2780 and IOSE, respectively), the mean number of TNTs formed per cell was also highest in these latter cell populations . This result could have been due to the sheer number of chemoresistant cells, leading to crowding in culture conditions that simply did not provide enough room for TNT growth.…”
Section: Tunneling Nanotubes: a Novel Drug Target For Cancer‐directedmentioning
confidence: 99%
“…The importance of cell cycle in the genesis of TNTs has yet to be explored. Work from our group investigating how TNTs form between cancer cells has shown that factors stimulating or suppressing TNT formation are not entirely dependent on the rate of cellular proliferation . Subtypes of TNTs have been described, including most commonly those that extend between cells located at short or long distances.…”
Section: Elucidating Modes Of Intercellular Communication: Tunneling mentioning
confidence: 99%